Hospital images : a clinical atlas - Aronowitz, Paul B. (Hospital medicine, current concepts., 2012)
This gorgeous, full-color atlas and case-book presents more than sixty cases with over one hundred associated, super high-quality clinical images that a physician needs to be able to rapidly recognize and know for accurate, expedient diagnosis and treatment. The images are presented with the patient's brief medical history, followed by the diagnosis, brief discussion of the diagnosis, and the patient's clinical course and treatment. These miniature case studies encompass photos and descriptions of patients, supporting physical findings, X-rays, CT scans, electrocardiograms, blood s.